CFD Simulation of Automotive Pollutant Dispersion in High-Rise Building Urban Environment Under Deeply Stable Atmospheric Condition - R. Lotfy, E; M. F. Wan Mahmood, W; Zulkifli, R; Harun, Z (International Journal of Engineering and Technology, 2018)
The layer of atmosphere adjacent to the earth’s surface which is affected by friction, heat transfer and pollution from the surface is called the atmospheric boundary layer (ABL). At nighttime, the earth’s surface become colder than the upper atmospheric layers. The thermal stratification with heavy cold layers close to the ground and light hot ones upwards dampens mixing currents in the atmosphere; a condition named as stable ABL. The absence of mixing at night causes the pollutants released from ground sources, such as automotive transportation, to settle in the layers close to the earth which affects human health. This research is a CFD investigation of the effect of building density on pollutant dispersion in urban areas under severe atmospheric stability condition. Three plane area densities were examined; 35, 25 and 15%. Carbon dioxide was considered as the pollutant. Large eddy simulation (LES) was utilized in the simulation. The results have proven the positive effect of building structures in dispersing pollutants. However, high building densities above 25% trap high concentrations of pollutants at the pedestrian level. The research may offer recommendations for the city planners and legislators about traffic pollution and architectural planning.